Diversifikasi Tanaman dalam Dusung: “Meningkatakan Keberlanjutan dan Kesejahteraan Petani Dusun Kranjang” - Wattimena, Cornelia. M. A.; Pietersz, Juglas H.; Latupapua, Lesly (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Kranjang Hamlet community is one of the hamlets located in the Wayame Village Administrative Area, Teluk Ambon District–Ambon City, where the majority of the community lives as farmers, especially vegetable farmers. However, the yields of vegetable crops are hampered, not optimal due to pest and disease attacks as well as the acidity level of their land. Therefore, in order for the vegetable farmers' harvests in Kranjang Hamlet to always be optimal, the Kranjang Hamlet community needs to be provided with training and education on how to utilize their land optimally. The method used in Community Service activities is through Community Outreach. Socialization activities can be held well and smoothly according to the activity plan that has been made. This activity is well received by the community. The material can be delivered thoroughly and at the end of the activity, participants have new insights regarding crop diversification in the Hamlet to improve the welfare of farmers.